FEASIBILITY OF REUSING PFF2 RESPIRATORS DURING THE COVID-19 PANDEMIC IN BRAZIL: QUASI-EXPERIMENTAL STUDY - Daniela Silva dos Santos Schneider; Ana Maria Müller de Magalhães; João Lucas Campos de Oliveira; Ana Karina Silva da Rocha Tanaka (Cogitare Enfermagem)
Objective: Evaluate the feasibility of decontaminating PFF2 respirators in pandemic situations.